Efficacy and safety of human immunoglobulin monotherapy in pediatric patients with multisystem inflammatory syndrome associated with COVID-19: a critical review of current evidence - Gálvez Arévalo, Ricardo Abraham (2022)
Objective: To determine the efficacy and safety of human immunoglobulin (HI) used as monotherapy, compared with corticosteroids, in pediatric patients with multisystem inflammatory syndrome (MIS) associated with COVID-19. Methods: systematic search carried out with evidence published up to April 20, 2022 in PubMed, The Cochrane Library and LILACS databases, the selection of documents focused on clinical practice guidelines (CPG), ETS, systematic reviews and clinical trials. randomized controlled trials (RCTs) in phase III. This process was complemented with a search on the web pages of organizations that carry out CPG and ETS. RCT registries were also consulted at www.ClinicalTrials.gov to identify any that are ongoing or not yet published. Results: Two CPGs prepared by the WHO and the NIH, an observational study and an ongoing phase III RCT, were analyzed. The WHO and the NIH do not recommend the use of HI in monotherapy for the treatment of SIM. An observational study found no difference between HI and corticosteroids in mortality, morbidity, and adverse events in pediatric MIS patients. Finally, a phase III RCT was identified in the process of recruiting pediatric participants with SIM, and it will seek to compare the effect of corticosteroids with HI. Conclusion: There is no evidence that the use of HI in monotherapy is more effective and safe than the use of corticosteroids in monotherapy for the treatment of pediatric patients with MIS associated with COVID-19.